Bifocal stress fracture of pubic rami after contralateral total hip arthroplasty and longstanding ipsilateral hip fusion - Aljinović, Ana (Array, 2009)
Abstract: In this case report we present a patient with bifocal pubic rami stress fractures after contralateral total hip arthroplasty for congenital hip dysplasia and longstanding ipsilateral hip fusion. Treatment protocol for patients with various degrees of hip arthritis on one side and contralateral longstanding hip fusion are proposed based on the literature and our and previously published cases